PRODUCTION OF CHEESE USING IMPROVED TECHNOLOGY FROM GOAT MILK - Rakhmatova S.M. (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
This article describes the production of uzbek cheese. One of the most famous pickled cheeses is brynza. Cheese is a Greek white cheese made from sheep or goat's milk. Since ancient times, it has been aged for almost two months until it acquired a salty or spicy taste. The population of Uzbekistan loves this cheese for its pleasant milky taste with creamy notes and a delicate but dense consistency.